Elective induction of labour in low risk nulliparous women at term: Caution is needed. (August 2019) - Ghi, Tullio; Dall'Asta, Andrea; Fieni, Stefania
Abstract: The recently published ARRIVE trial demonstrated that "policies aimed at the avoidance of elective labour induction among low-risk nulliparous women at 39 weeks of gestation are unlikely to reduce the rate of caesarean delivery on a population level". In this commentary we discuss some controversial aspects of the study that in our opinion may undermine its validity at wide population level.